Efficacy of Tunnel Technique (TUN) versus Coronally Advanced Flap (CAF) in the Management of Multiple Gingival Recession Defects: A Meta-Analysis - Frank Mayta-Tovalino; Joshuan J. Barboza; Vinay Pasupuleti; Adrian V. Hernandez (International Journal of Dentistry)
Objective. We systematically assessed the efficacy of tunnel technique (TUN) vs. coronally advanced flap (CAF) in the management of multiple gingival recession defects in adults. Methods. Five databases were searched until September 2021 for randomized controlled trials (RCTs) assessing TUN vs. CAF; grafts of interest were acellular dermal matrix (ADM) and connective tissue graft (CTG). Primary outcomes were root coverage (RC) and complete root coverage (CRC). Secondary outcomes were clinical attachment level (CAL), keratinized tissue width (KTW), probing depth (PD), and recession coverage (REC). Effect measures were risk ratio (RR) or mean difference (MD) with their confidence intervals (95% CI). Inverse variance methods and random-effects model meta-analyses were used. Subgroup analyses by the type of graft were performed. Quality of evidence was assessed using GRADE methodology. Results. Five RCTs (n = 173) were included, with a follow-up of 6 months for all outcomes. In comparison to CAF, TUN did not significantly reduce CRC (RR 0.65; 95% CI 0.002–176.7; p=0.51) and did not increase RC (MD 0.99%; 95% CI −6.7 to 8.6; p=0.80). In comparison to CAF, TUN showed no significant reduction of secondary outcomes. Subgroup analyses by type of graft showed no differences in comparison to primary analyses for primary and secondary outcomes. Three RCTs had a high risk of bias, and five RCTs had very low quality of evidence for all outcomes. Conclusions. In adults with gingival recessions, TUN had similar primary and secondary outcomes in comparison with CAF. Subgroup analyses by the type of graft did not affect main conclusions. More RCTs with better design are needed to further characterize the effects of TUN vs. CAF in the treatment of multiple gingival recession defects.